A study of the changes in management tasks - Bilanics, Ágnes (Acta Agraria Debreceniensis, 2008)
Determining the scope of management is difficult owing to the terminological uncertainty, which can be experienced often. The terms of management theory are interpreted differently not only by the general public but also by the highly recognised specialists, researchers, and instructors of this special area. The reasons for this can be found in historical preliminaries, the different social environment, attitude and approach. The definitions and the content of the terms have been modified and developed in parallel with the social and economic changes (Berde, 2001). The consequences of the economic changes of the past decade have significantly affected the conditions for the operation of management, the management structures, the ranking and importance of management tasks. The differentiating of corporate sizes, the increase in the number of small and medium-sized enterprises, the simplification of the production structure, the decrease in management levels, the strengthening of proprietary positions, and the continuous changing of the market economic environment are all influences that also affect, determine and continuously modify the management tasks.Everyone knows what a manager does. Still, it is not easy to determine what it does all day as his or her work is such a complex activity where the management tasks are present in a complex way, weaved into each other. Nevertheless, the separate management tasks appearing in the management activity can be defined well, can be separated from each other clearly, enabling us to study and analyse each management task separately.Based upon the findings of a face-to-face questionnaire survey, this essay aims to present that, according to the managers, to what extent the judgement of management tasks has changed and to what extent the applied management tasks specialise based upon the extent of relation to the company.